Nanobubbles activate anaerobic growth and metabolism of Pseudomonas aeruginosa - Miu Ito (Nature Portfolio, 2021)
Abstract The effect of nanobubbles on anaerobic growth and metabolism of Pseudomonas aeruginosa was investigated. P. aeruginosa grew earlier in the culture medium containing nanobubbles and the bacterial cell concentration in that culture medium was increased a few times higher compared to the medium without nanobubbles under anaerobic condition. Both gas and protein, which are the metabolites of P. aeruginosa, were remarkably produced in the culture medium containing nanobubbles whereas those metabolites were little detected in the medium without nanobubbles, indicating nanobubbles activated anaerobic growth and metabolism of P. aeruginosa. The carbon dioxide nanobubbles came to be positively charged by adsorbing cations and delivered ferrous ions, one of the trace essential elements for bacterial growth, to the microbial cells, which activated the growth and metabolism of P. aeruginosa. The oxygen nanobubbles activated the activities of P. aeruginosa as an oxygen source.